Strategic Marketing Approaches Leveraging the 7P Marketing Mix Framework to Overcome Sales Challenges and Enhance Purchase Intention for IELTS Programs at Athena English Course - Ilman Sadri; Atik Aprianingsih (Utan Kayu Publishing, 2025)
Athena English Course, an English course institution in Bandung, faces challenges in increasing the number of registrants, especially in online IELTS preparation classes. This study aims to analyze the influence of the 7P marketing mix elements-Product, Price, Place, Promotion, People, Process, and Physical Evidence-on customer purchase intention in choosing an online IELTS preparation course. The research approach used is a mixture of qualitative and quantitative methods, with data collection through respondent surveys. The data obtained were analyzed using SmartPLS to evaluate the significance of the relationship between variables. The results showed that Price, Promotion, Product, and People elements have a positive influence on customer purchase intention, while Place, Process, and Physical Evidence elements have a weaker or insignificant impact.The findings provide insights for English course providers in designing more effective marketing strategies to attract more students and increase sustainable business growth. Based on the research results, Athena English Course can optimize 3 main strategies, namely first, focusing on new market segmentation that is more specific and has minimal competitors, second, utilizing social media marketing promotions, and third, readjusting the price of the products offered to compete with competitors and reach a wider market. With a more targeted approach, Athena English Course has the potential to increase its revenue and competitiveness in the English language education industry in Indonesia.